Maslahah As An Islamic Source And Its Application In Financial Transactions - Muhammad Ridhwan Ab. Aziz; Elvan Syaputra; Faridl Noor Hilal; Muhammad Febriansyah; Issa Qaed; Muhammad Majdy Amiruddin (Quest Journals Inc., 2024)
Quest Journals Journal of Research in Humanities and Social Science Volume 2 ~ Issue 5 (2014) pp: 66-71